Analysis of Boiler Efficiency and NPHR With the Use of Sootblower in a 315 MW Coal-fired Power Plant - Utama, Tri Yoga; Ruhyat, Nanang (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
In the power generation sector, particularly in Indonesia, coal-fired power plants remain a key source of electricity. The Lontar Extension Coal-Fired Steam Power Plant (PLTU) (1x315 MW) is a significant facility that plays a critical role in ensuring a stable electricity supply to the Jakarta area and its surroundings. One of the major operational challenges faced by the plant is managing the ash produced during coal combustion, which leads to slagging and fouling on boiler tube surfaces. These phenomena impair heat transfer efficiency and increase fuel consumption. Given the growing emphasis on operational efficiency and sustainability in the power generation industry, addressing these challenges is of paramount importance. In this research, we conduct a comprehensive analysis of key performance parameters, such as Net Plant Heat Rate (NPHR) and boiler efficiency, at the Lontar Extension PLTU. A particular focus is placed on the use of soot blowers in the Heat Recovery Area (HRA) to mitigate slagging and fouling issues. This study offers unique insights by quantifying the benefits of soot blower operation, which resulted in a 0.71% increase in boiler efficiency and a 33.91 kcal/kWh decrease in NPHR at 100% load, and a 0.63% increase in boiler efficiency and 47.16 kcal/kWh reduction in NPHR at 50% load. Additionally, the soot blowers contributed to increased net power output and reduced coal consumption, highlighting the innovation in boiler cleaning techniques and their significant impact on fuel efficiency.